2005
DOI: 10.1080/03014460500228626
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations of the apolipoprotein B gene in Turkish patients with coronary artery disease

Abstract: Apo B EcoRI genotypes were not found as risk factors for CAD, whereas XbaI TT genotype was detected to prevent against CAD in our study group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Though those results are contradictory, such an association may tend to be more frequent in Asians, compared with Europeans, because of unavailable data on Europeans. At the Ins/Del and EcoRI sites, data showing no association with every variety of plasma lipid and lipoprotein have been reported frequently (Xu et al 1990;Renges et al 1991;De Benedictis et al 1991;Mendis et al 1991;Hixson et al 1992;Anderson et al 1997;Delghandi et al 1999;Duman et al 2005). …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Though those results are contradictory, such an association may tend to be more frequent in Asians, compared with Europeans, because of unavailable data on Europeans. At the Ins/Del and EcoRI sites, data showing no association with every variety of plasma lipid and lipoprotein have been reported frequently (Xu et al 1990;Renges et al 1991;De Benedictis et al 1991;Mendis et al 1991;Hixson et al 1992;Anderson et al 1997;Delghandi et al 1999;Duman et al 2005). …”
Section: Discussionmentioning
confidence: 93%
“…If the data of ambiguous haplotypes are added, the relationship between both ethnic populations may be different. The associations of APOB polymorphisms with quantitative levels of plasma lipid and lipoprotein have been noted, especially among the patient group with cardiovascular disease or hypercholesterolemia (Hansen et al 1994;Delghandi et al 1999: Guzman et al 2000Machado et al 2001;Boekholt et al 2003;Jemaa et al 2004;Duman et al 2005). This has also been found in normolipidemic healthy populations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There were five studies that did not follow the HWE. 13,16,20,34,51 The NOS results indicated that the methodological quality was generally good.…”
Section: Study Characteristicsmentioning
confidence: 98%
“…13 Duman et al did not observe significant differences in the frequencies of apoB XbaI (CC, CT, TT) and EcoRI (AA, AG, GG) genotypes between case and control subjects in Turkish. 20 Gallegos-Arreola et al detected that the apoB XbaI (CC) genotype is associated with CAD patients in the Mexican population. 21 Kallel et al found a significant but not independent association between the Ins/Del polymorphism of the apoB gene and MI in the Tunisian population.…”
Section: Discussionmentioning
confidence: 99%